Hadith #2163 - Jami' al-Tirmidhi - Abdur Rahman bin Yazid bin Jabir عبد الرحمن بن يزيد بن جابر الأزدي; Abu Hurairah; Abu Salah al-Ash'ry al-Shamy أبو صالح الأشعري الشامي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد (Jami' al-Tirmidhi)
“Whoever prays Subh, then he is under the protection of Allah’s covenant, so do not infringe at all upon Allah’s covenant.”
Grade:

Hadith #491 - Sunan Ibn Majah - Abu 'Abdullah al-Ash'ry أبو عبد الله الأشعري; Abu Salah al-Ash'ry al-Shamy أبو صالح الأشعري الشامي; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Khalid bin al-Walid; Mamtur Abu Salam al-Aswad ممطور أبو سلام الأسود الحبشي; Shayba bin al-Ahnf al-Awza'y شيبة بن الأحنف الأوزاعي أبو النضر الشامي; Shurahbil bin Hasana; Yazid bin Abi Sufyan (Sunan Ibn Majah)
“The Messenger of Allah said: ‘Whoever removes something harmful from the mosque, Allah will build for him a house in Paradise.'”
Grade:

Hadith #3597 - Sunan Ibn Majah - Abdur Rahman bin Yazid bin Jabir عبد الرحمن بن يزيد بن جابر الأزدي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Abu Salah al-Ash'ry al-Shamy أبو صالح الأشعري الشامي; Hammad bin Usamah حماد بن أسامة - أبو أسامة (Sunan Ibn Majah)
“I heard the Messenger of Allah (saas) say: ‘The supplication of a father reaches the Veil (i.e. the place of repentance).'”
Grade: